Ausencia de vínculo social en Goffman - Ribes, Alberto J. (El Colegio de México, 2024)
In this paper, we focus on problematic situations in which individuals are subjected to a series of stresses: interactional alienation may occur, shame may occur, or character clashes may occur. In all these situations, individuals have to navigate the dynamics of the social in adverse circumstances. However, despite what might seem otherwise, for Goffman these incidents are more the norm than the exception. What is exceptional is that social situations pass smoothly and that the feeling of euphoria is generated and reinforce both individuals an the social order and strengthens the sense of reality. The norm in individuals striving to try to achieve that result, but very often encountering serious difficulties that require them to do a constant job of presenting themselves.